Manajemen Perubahan Organisasi sebagai Upaya Peningkatan Kinerja Perusahaan di Minuman Qiuqiunian - Preti Intan Sari; Nuri Aslami (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
The aims of this study were: (1) Identifying the causes of organizational change that occurred in the QIUQIUNIAN beverage business. (2) Identify the impact of organizational change on the QIUQIUNIAN beverage business. (3) Analyzing the process of organizational change that occurs in the QIUQIUNIAN beverage business. (4) Analyzing the factors supporting organizational change in the QIUQIUNIAN beverage business. The results of the study concluded that the causes of organizational change: (1) due to the fulfillment of consumer needs and tastes, (2) competition from drink entrepreneurs, (3) due to fluctuating economic conditions in Indonesia. (4) There are problems with education and financial capacity in the QIUQIUNIAN beverage business, (5) environmental factors. The process of implementing changes that occur in the QIUQIUNIAN beverage business in general is of the same character, namely a calm and orderly character in evolution or stages (Midle of change). Factors supporting change include: (1) the government, (2) company policies, (3) the Materials used to innovate in the manufacturing process are easy to obtain. Sources of resistance to organizational change include: (1) concerns about the emergence of new competitors, (2) the variety of ideas or ideas of drink entrepreneurs.